Reading philosophy selected texts with a method for beginners - Guttenplan, Samuel D.; Hornsby, Jennifer; Janaway, Christopher; Schwenkler, John (Reading philosophy, 2021)
Philosophy is intriguing even to those who know little of it. But the sort of philosophy studied at universities is difficult to enter into on one's own. Reading Philosophy was designed to overcome this difficulty. It is a book for those who want genuinely to engage with the subject, either on their own or in the context of taught introductory courses"--Provided by publisher.